IMPROVING THE TECHNOLOGY OF COMPLEX REFINING OF COTTONSEED OIL - Khamraqulova Muborak Khakimovna; Saydullayeva Dilrabo Ravshanjon qizi (Modern American Journals, 2025)
This article is dedicated to the scientific improvement of the technology for deep and complex refining of cottonseed oil. Within the framework of the study, existing refining processes, their technological stages, and efficiency levels were analyzed. The content of undesirable components typically found in cottonseed oil—such as phosphatides, pigments, and free fatty acids—was examined, along with methods for their effective removal. Particular attention was given to optimizing physicochemical methods, especially the enhancement of process parameters in neutralization, hydration, and deodorization stages. Based on the proposed technological solutions, experimental methods were developed and tested. The results obtained led to the formulation of an updated refining process. The research outcomes are recommended for application at the industrial scale and contribute to improving the quality of refined cottonseed oil.
Keywords: Cottonseed oil, refining, alkaline solutions, neutralization, physicochemical treatment, technological optimization.